Risk factors for surgical site infections with the Sinus Tarsi Approach in displaced intra-articular calcaneal fractures; a prospective cohort study with a minimum of one year follow-up. Issue 7 (July 2020) - Spierings, K.E.; Sanders, F.R.K.; Nosewicz, T.L.; Schepers, T.
Abstract : The risk of SSIs in DIACFs treated via STA is low. Significant predictors for SSIs are surgery within one week, ASA classification of 2 or higher and blood loss of more than 150 cc. Abstract: Background: In the last decade, the sinus tarsi approach (STA) has gained interest over the extensile lateral approach (ELA) in the operative treatment of displaced intra-articular calcaneal fractures (DIACF's), mainly because of the lower rate of surgical site infections (SSIs). However, most studies are small and retrospective. The aim of this study was to evaluate the rate of SSIs of the STA in a large, prospective series of patients and to identify predictors for SSIs. Methods: In this prospective cohort study, all consecutive patients who were operatively treated for a DIACF in our Level 1 trauma center between August 2012 and January 2019 were included and followed for at least one year. All operative procedures were performed by two specialized foot and ankle trauma surgeons using the STA. Using multinomial logistic regression, risk factors for SSIs were identified. Results: A total of 237 calcaneal fractures in 214 patients were included, of which 179 underwent open reduction and internal fixation and 58 a primary arthrodesis. Most patients were male (73.6%) and the mean age was 45.9 years. There were 16 patients that developed a SSI (6.8%), of which 9 (3.8%) were deep and 7 (3%) were superficial infections. The multivariate analysis pointed out that surgery within one week after injury increased the chance of a SSI, as well as an ASA of 2 or higher and more than 150 cc of blood loss during the procedure. Conclusion: This study confirms the low risk of SSI in DIACFs treated via STA. Significant predictors for SSIs were surgery within one week after injury, ASA of 2 or higher and blood loss > 150cc.